Encapsulamento de Azospirillum brasilense em matriz a base de carboximetilcelulose e trealose para melhoria da viabilidade - Merlini, William (Universidade Federal de São Carlos, 2025)
Inoculation of cultivars with diazotrophic bacteria such as Azospirillum brasilense can make crops more productive and sustainable, since it reduces the need for nitrogenous chemical fertilizers. However, it is necessary to develop bioinoculant formulations that maintain cell viability for long periods and provide protection against biotic and abiotic stresses. Osmotic, saline, radiation and temperature stresses represent challenges for the prevalence of A. brasilense cells in soil. As an alternative to this problem, the aim is to encapsulate A. brasilense cells in biodegradable matrices through the ionotropic gelation method, characterize the material and assess cell viability during storage. The method consists of forming macrobeads of the matrices containing the microorganism, through the dripping and crosslinking of a polymeric dispersion in a FeCl3 solution. The material chosen was carboxymethyl cellulose (CMC) because it is a renewable, abundant and commercial material and trehalose because of its thermal protection capacity. Beads with a fixed amount of 2.5% CMC and 4 treatments containing 0%, 1%, 5% and 10% trehalose were produced and stored moist at 4 °C and 25 °C; and after drying at 25 °C. The CMC capsules without trehalose showed higher encapsulation efficiency and better viability up to the 15th day of storage at 25 °C. FTIR analysis evidenced the formation of the chemical structure of CMC crosslinking with Fe³⁺, and SEM analysis revealed a regular surface of the spheres. However, the formulation of Azospirillum inoculants requires further investigation, particularly regarding the optimal concentrations of CMC and trehalose and their influence on matrix stability and cell survival during prolonged storage.
Encapsulation of Azospirillum brasilense in a carboxymethylcellulose and trehalose-based matrix to improve viability
Keywords: Azospirillum brasilense; Inoculantes; Encapsulamento; Carboximetilcelulose; Trealose; Inoculants; Encapsulation; Carboxymethylcellulose; Trehalose; ENGENHARIAS::ENGENHARIA QUIMICA; 2. Fome Zero e Agricultura Sustentável